Modulation of B lymphocyte function by an aqueous fraction of the ethanol extract of Cissampelos sympodialis Eichl (Menispermaceae) - Alexandre-Moreira,M.S. (2003)
Cissampelos sympodialis Eichl species are used in folk medicine for the treatment of asthma, arthritis and rheumatism. In the present study, we investigated the immunomodulatory effect of an aqueous fraction of a 70% (v/v) ethanol extract of C. sympodialis leaves on B lymphocyte function. The hydroalcoholic extract inhibited the in vitro proliferative response of resting B cells induced by LPS (IC50 = 17.2 µg/ml), anti-delta-dextran (IC50 = 13.9 µg/ml) and anti-IgM (IC50 = 24.3 µg/ml) but did not affect the anti-MHC class II antibody-stimulated proliferative response of B cell blasts obtained by stimulation with IL-4 and anti-IgM. Incubation with the hydroalcoholic extract used at 50 µg/ml induced a 700% increase in intracellular cAMP levels. IgM secretion by resting B cells (obtained from normal mice) and polyclonally activated B cells (obtained from Trypanosoma cruzi-infected animals) was inhibited by the hydroalcoholic extract. The latter were more sensitive to the hydroalcoholic extract since 6.5 µg/ml induced a 20% inhibition in the response of cells from normal mice while it inhibited the response of B cells from infected animals by 75%. The present data indicate that the alcoholic extract of C. sympodialis inhibited B cell function through an increase in intracellular cAMP levels. The finding that the hydroalcoholic extract inhibited immunoglobulin secretion suggests a therapeutic use for the extract from C. sympodialis in conditions associated with unregulated B cell function and enhanced immunoglobulin secretion. Finally, the inhibitory effect of the hydroalcoholic extract on B cells may indicate an anti-inflammatory effect of this extract.